Nonstandard approach to the ischemic stroke treatment - K. M. Vakhitov; P. A. Vladimirov; N. V. Zukovskaya; A. F. Kuvazhukova; E. G. Kmetik (Вестник хирургии имени И.И. Грекова)
Ischemic stroke is one of the most common causes of disability and mortality worldwide. Occlusive-stenotic lesion of the extra- and intracranial carotid arteries, which developed acutely and led to acute cerebrovascular accident, is a prognostically unfavorable factor. The appearance of endovascular technologies has revolutionized the salvation of this category of patients; however, they are sometimes powerless in the fight against nature. The article presents a case of tandem and bilateral lesions of the extra- and intracranial internal carotid artery, the successful result of treatment of which became possible only due to the development of spontaneous recanalization.